The effect of lavender oil inhalation on pain, anxiety, and sleep quality after coronary artery bypass graft: a randomized controlled trial protocol - DİKMEN AYDIN, YEŞİM; GÜRKAN, AYSEL (My University, 2022)
Background: Pain, anxiety, and sleep disorders are common side effects of coronary artery bypass graft (CABG) surgery. Although pharmacological agents are currently used in the treatment of these problems, in addition to their undesirable side effects, they increase healthcare costs, and their inadequate control leads to morbidities, prolonged hospital stay and increased burden of care. Therefore, supportive interventions are needed. The aim of this study is to determine the effect of lavender oil inhalation on the pain intensity, anxiety and sleep quality of patients that underwent CABG surgery.Methods: This study was planned as a prospective randomized controlled trial. Participants meeting the inclusion criteria will be randomly assigned to the intervention and control groups. During the hospitalization period after CABG surgery, 2% lavender oil (Lavandula angustifolia) inhalation will be applied to the intervention group three times a day, while the control group will only receive routine care. The pain intensity of the groups will be evaluated with the numeric rating scale, anxiety levels with the state-trait anxiety inventory, and sleep quality with the Richards-Campbell sleep questionnaire.Conclusions: There is a need for new approaches to improve the physiological and psychological health of patients after CABG surgery and help them return to their daily life activities and social lives in a shorter time. This trial will allow for the assessment of the effects of this intervention and provide valuable evidence to guide clinical practice.Trial registration: This trial was registered in May, 2022 (NCT05377983).
Keywords: Hemşirelik; Sağlık Bilimleri; Nursing; Health Sciences; Klinik Tıp (MED); Klinik Tıp; HEMŞİRELİK; Clinical Medicine (MED); CLINICAL MEDICINE; NURSING; Farmakoloji (hemşirelik); Onkoloji (hemşirelik); Asistan Hemşirelik; Tıbbi ve Cerrahi Hemşirelik; Annelik ve Ebelik; LPN ve LVN; Acil Tıp Hemşireliği; Yoğun Bakım Hemşireliği; İleri ve Uzman Hemşirelik; Hemşirelik (çeşitli); Genel Hemşirelik; Pharmacology (nursing); Oncology (nursing); Nurse Assisting; Medical and Surgical Nursing; Maternity and Midwifery; LPN and LVN; Emergency Nursing; Critical Care Nursing; Advanced and Specialized Nursing; Nursing (miscellaneous); General Nursing